Women have a worse prognosis and undergo fewer coronary angiographies after out-of-hospital cardiac arrest than men. Issue 5 (August 2018) - Winther-Jensen, Matilde; Hassager, Christian; Kjaergaard, Jesper; Bro-Jeppesen, John; Thomsen, Jakob H; Lippert, Freddy K; Køber, Lars; Wanscher, Michael; Søholm, Helle
Background: Out-of-hospital cardiac arrest is more often reported in men than in women. Objectives: We aimed to assess sex-related differences in post-resuscitation care; especially with regards to coronary angiography, percutaneous coronary intervention, mortality and functional status after out-of-hospital cardiac arrest. Methods: We included 704 consecutive adult out-of-hospital cardiac arrest-patients with cardiac aetiology in the Copenhagen area from 2007–2011. Utstein guidelines were used for the pre-hospital data. Vital status and pre-arrest comorbidities were acquired from Danish registries and review of patient charts. Logistic regression was used to assess differences in functional status and use of post-resuscitation care. Cox regression was used to assess differences in 30-day mortality. We used 'smcfcs' and 'mice' imputation to handle missing data. Results: Female sex was associated with higher 30-day mortality after adjusting for age and comorbidity (hazard ratio (HR): 1.42, confidence interval (CI): 1.13–1.79, p <0.01), this was not significant when adjusting for primary rhythm (HR: 1.12, CI: 0.88–1.42, p =0.37). Women less frequently received coronary angiography <24 h in multiple regression after out-of-hospital cardiac arrest (odds ratio (OR)CAG =0.55, CI: 0.31–0.97, p =0.041), however no difference in percutaneous coronary intervention was found (ORPCI =0.55, CI: 0.23–1.36, p =0.19). Coronary artery bypass grafting was less often performed in women (ORCABG : 0.10, CI: 0.01–0.78, p =0.03). There was no difference in functional status at discharge between men and women ( p =1). Conclusion: Female sex was not significantly associated with higher mortality when adjusting for confounders. Women less often underwent coronary angiography and coronary artery bypass grafting, but it is not clear whether this difference can be explained by other factors, or an actual under-treatment in women.